(untitled) (Dhaka Shishu (Children) Hospital Journal, 2021)
Patent ductus arteriosus is one of the common congenital acyanotic heart disease in neonates, especially in preterm. Patent ductus arteriosus (PDA) is a congenital condition, characterized by a persistent connection between the aorta and the pulmonary artery. Patency of Ductus Arteriosus is essential for fetal survival. Patent ductus arteriosus is one of the most common clinical findings and most frequent source of complications in premature infant. After birth, in term infants, the ductus usually closes within the first day of life, starting with functional closure followed by anatomical closure with vascular remodeling. The persistence of the PDA in preterm infant is inversely related to gestational age and birth weight. The incidence of Patent Ductus Arteriosus is 31% in preterm infant weighing 501 to 1500 gm and gestational age 29 weeks. The treatment options available are conservative medical management, pharmacological therapy or surgical ligation. Conservative medical management involves fluid restriction; watchful waiting and ventilator support. DS (Child) H J 2020; 36(1) : 61-66